Pengembangan Materi Pembelajaran Pada Pembelajaran PJOK Kelas V Sekolah Dasar (Universitas Negeri Semarang, 2022)
The purpose of this research is to produce a learning development product in the form of coket. This research method uses quantitative and qualitative approaches with Research and Development methods. Data collection techniques through observation, questionnaires and questionnaires. The results of this study obtained the results of a small group trial of 86% with the number of subjects 28 students based on the established criteria, so they have met the good criteria. Then obtained the results of a large-scale trial of 92% with the number of subjects 92 people. Based on the established criteria, it has met the very good criteria. Based on the results of data analysis and evaluation of PJOK experts, an average percentage of 93% was obtained, while the results of data analysis from PJOK teachers obtained an average of 91%. The conclusion of this study is that the development of the basketball learning model reached a good category with an average student questionnaire of 89%.